Crop scheduling improvements for rainfed agriculture in the high jungle of Peru - Meseth, Enrique (2014)
This work was aimed to improve the water management for agriculture by applying efficient crop schedules in Vilcabamba and similar areas of the high jungle, which can satisfy most of the water requirements with rainfed agriculture to maximize the crops yield. For this purpose, two field practices were carried out during the dry (September 2012) and wet season (February 2013) to measure rivers and canals flows with the velocity/area method; 19 soil samples were collected on-site and analyzed, presenting prevalent sandy loam and loam textures. Cropwat program was used to estimate crop water requirements and scheme irrigation requirements, resulting in a maximum flow capacity of 1.72 l s-1 in May, during the dry season. The flow capacity can be satisfied, since small ditches convey approximately 2 to 6 l s-1 on the same season. The research findings indicate that rainfed farming can be practised, yet an initial pre-irrigation needs to be applied, for crops should not be water stressed. However, if soil is not pre-irrigated the production can be affected, with vegetables and potato crop yields being reduced by 4.7% and 1.4% respectively. To minimize these effects, both crops are suggested to be sowed one month later, adapting their growth period to the rainy season.